Chemical Extraction of Copper from Copper Sulphide Ores of Pakistan by Roast Leach Method: Copper Extraction from Copper Sulphide Ores (Biological Sciences - PJSIR, 2010)
Copper ores, containing both complex sulphide minerals and those containing chalcopyrite mineral, were studied for the extraction of copper by leaching after roasting. Roasting at 650 °C for 30 min rendered the ore leachable in dilute sulphuric acid of 2.5% concentration. The process of metal extraction would be of hydrometallurgical importance for low to high grade sulphide and polymetallic complex sulphide ores occurring in Pakistan. The kinetic models of roasting reaction fit phase boundary as well as diffusion reaction mechanism.